Two-dimensional Cu2Si monolayer with planar hexacoordinate copper and silicon bonding - Yang, Li-Ming; Bacic, Vladimir; Popov, Ivan A.; Boldyrev, Alexander I.; Heine, Thomas; Frauenheim, Thomas; Ganz, Eric (Journal of the American Chemical Society, 2015)
Two-dimensional (2D) materials with planar hypercoordinate motifs are extremely rare due to the difficulty in stabilizing the planar hypercoordinate configurations in extended systems. Furthermore, such exotic motifs are often unstable. We predict a novel Cu2Si 2D monolayer featuring planar hexacoordinate copper and planar hexacoordinate silicon. This is a global minimum in 2D space which displays reduced dimensionality and rule-breaking chemical bonding. This system has been studied with density functional theory, including molecular dynamics simulations and electronic structure calculations. Bond order analysis and partitioning reveals 4c-2e σ bonds that stabilize the two-dimensional structure. We find that the system is quite stable during short annealing simulations up to 900 K, and predict that it is a nonmagnetic metal. This work opens up a new branch of hypercoordinate two-dimensional materials for study.
CRIS-Team Scopus Importer:2023-03-20